Homortomyces gen. nov., a new dothidealean pycnidial fungus from the Cradle of Humankind - Michael J. Wingfield; Lorenzo Lombard; Johannes Z. Groenewald; Pedro W. Crous (IMA Fungus)
Homortomyces is introduced as a new coelomycetous genus associated with leaf spots on Combretum erythrophyllum trees growing near and around the Sterkfontein caves, Maropeng, South Africa. Based on its transversely septate, brown conidia, the presence of paraphyses, and percurrent proliferation of the conidiogenous cells, the genus resembles Stilbospora (Melanoconidaceae, Diaporthales). It is distinct in having pycnidial condiomata, conidia lacking mucoid sheaths, and becoming muriform when mature. Its morphology and phylogenetic placement based on analyses of sequence data for the large subunit nuclear ribosomal RNA gene (LSU, 28S) as well as the ITS and 5.8S rRNA gene of the nrDNA operon, show that Homortomyces represents a novel genus in Dothideomycetes, although its familial relationships remain unresolved.